2020
DOI: 10.1002/slct.201904629
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Metal‐Organic Framework Derived ZnO/Ni0.9Zn0.1O Nanocomposites for Improved Photocatalytic Degradation of Organic Dyes

Abstract: An optimized structure is of considerable importance for nickle oxide (NiO)‐based materials to achieve high performance as catalyst for contaminant degradation due to the inherent large band gap. Herein, a series of hybrids of NiO nanoparticles doped with zinc oxide (ZnO) semiconductor were fabricated via a facile one‐step calcination of bimetallic metal‐organic frameworks with varied Ni2+/Zn2+ molar ratios (MOF‐NiZn). It is worth noting that partial positions of Ni in NiO lattice are replaced by Zn to form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Also, the energy gaps (E g ) of TiO 2 and Sn 4+ /TiO 2 -BB50/70 samples were obtained according to the equation of ahn = A(hn À E g ) 2 (where a is the adsorption coefficient, h is Planck's constant, n is the light frequency, and A is energy independent constant). 22 The calculated E g value for Sn 4+ /TiO 2 -BB50/70 is smaller than that of TiO 2 (inset in Fig. S7a, ESI †), further demonstrating the improved photocatalytic performance of the Sn 4+ /TiO 2 -BB50/70 sample.…”
Section: Resultsmentioning
confidence: 92%
“…Also, the energy gaps (E g ) of TiO 2 and Sn 4+ /TiO 2 -BB50/70 samples were obtained according to the equation of ahn = A(hn À E g ) 2 (where a is the adsorption coefficient, h is Planck's constant, n is the light frequency, and A is energy independent constant). 22 The calculated E g value for Sn 4+ /TiO 2 -BB50/70 is smaller than that of TiO 2 (inset in Fig. S7a, ESI †), further demonstrating the improved photocatalytic performance of the Sn 4+ /TiO 2 -BB50/70 sample.…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure 4 (XO) and in Figure 5 (TC), the tests were performed at the solution concentration of 30 mg/L. It is well known that the active species produced by the catalysts have a strong effect on removal of pollutant molecules [16] . The results showed that the removal efficiency of pollutants increased when adding more photocatalysts.…”
Section: Resultsmentioning
confidence: 97%
“…It is well known that the active species produced by the catalysts have a strong effect on removal of pollutant molecules. [16] The results showed that the removal efficiency of pollutants increased when adding more photocatalysts. This can be explained from two aspects.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The binding energy of 22.9 eV between the two peaks verifies a +2 valence for Zn in O-ZMO/rGO. 11,34 In the high-resolution Mn 2p spectrum, the two major peaks can be deconvoluted into four peaks with binding energies of 641.1, 642.7, 652.7, and 654.2 eV (Fig. 2b), which demonstrates the co-existence of +2 and +3 valences.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 98%